Construction of a novel highly porous BiOBr/CsxWO3@SiO2 composite aerogel: Adsorption/self-heating photocatalytic synergistic degradation of antibiotics and mechanism study. Issue 3 (June 2022) - Li, Tianci; Liu, Jingxiao; Shi, Fei; Song, Xiaoying; Zhang, Haoyuan; Zhang, Haojie; Ma, Chuangchuang; Zhu, Keya; Liu, Junyan
Abstract: Adsorption and photocatalytic degradation of pollutants are both considered to be effective ways of removing pollutants from environment. Here, a novel highly porous BiOBr/Csx WO3 @SiO2 composite aerogel with adsorption/self-heating photothermal catalysis synergistic effect was constructed using melamine resin as template. Multiple detection results demonstrated that the template melamine resin is conducive to expanding pore volume of the composite aerogels. Moreover, owing to the high pore volume and excellent photothermal conversion as well as the BiOBr/Csx WO3 heterojunction catalysis effect, the composite aerogel with BiOBr/Csx WO3 molar ratio 2:1 exhibited the most efficient removal of antibiotic tetracycline from water, with the adsorption/self-heating photothermal catalytic degradation rate of tetracycline being close to 100% after 30 min of darkroom adsorption and 60 min of light irradiation, and it also showed high removal efficiency of other pollutants. The efficient adsorption/self-heating photothermal synergistic catalysis mechanism and photocatalytic degradation pathway of tetracycline have been analyzed. This work will provide a new idea for constructing SiO2 -based composite aerogel photocatalytic materials and the adsorption/self-heating photothermal catalytic synergetic effect will be a promising way for environment purification. Graphical Abstract: ga1 Highlight: BiOBr/Csx WO3 @SiO2 composite aerogels with high pore volume were constructed. The addition of melamine resin can help to obtain highly porous composite aerogel. The composite aerogel shows adsorption/photothermal catalytic synergistic effect. The BiOBr/Csx WO3 heterojunction can greatly improve the photothermal catalysis. The mechanism of self-heating photothermal synergistic catalysis has been analyzed.